Time and method of application of herbicides for semi-dry rice (Oryza sativa) - BHARGAVI, K; REDDY, T YELLAMANADA (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during rainy seasons of 1986 and 1987 to study the influence of time and method of application of different herbicides on semi-dry rice (Oryza sativa L.). The crop was grown rainfed initially and later converted into irrigated lowland rice. !'luple nutsedge (Cyperus rotundus L.) wasthe doininant weed during initial stages of crop growth, but barnyard grass [Echinochloa crus-galli (L.) P. Beauv.] dominated 40 days after sowing. Weed population WaS less (23.3/m2 ) with pre-emergence application of butachlor @ 1.5 kg ai/ha than that recorded in the unweeded control plots (179.1/m2). Drymatter of weeds at 60 days after sowing was lower (346 kg/ha) with pre-emergence application of butachlor than in the control (2 906 kg/ha). Post-emergence application of 2,4-D sodium salt.@ 0.9 kg ai/ha was less effective in controlling weeds compared with pre-emergence butachlor. Leaf-area index at 40 days after sowing was 2.1 with pre-emergence butachlor but was only 0.3 with the control. Dry matter of the crop at flowering was 3 583 kg/ha with pre-emergence butachlor and was only 196 kg/ha with the control. All the yield attributes, grain yield and straw yield were significantly higher with pre- emergence butachlor, early post-emergence (7 days after sowing) application of 2,4-Dethylester and 2 hand-weedings. Butachlor gave more grain yield (2536 kg/ha)Â· when sprayed than when applied with sand (1 737 kg/ha).